A Cognitive Ergonomics Framework of Smartphone User Interface Design for Late Adulthood Users - Yahya, Alfandi Nugroho (Curtin University, 2019)
A comparative study will engage with elderly participants in two different geographic or cultural locations - Australia and Indonesia. Each group must be over 70 years of age, and either still working professionally or active in a volunteer organisation. The study invites elderly participants to actively participate in identifying the specific features they would like to see included in a new phone design that would match their daily needs in their professional and personal life.